2018
DOI: 10.1186/s13643-018-0692-y
|View full text |Cite
|
Sign up to set email alerts
|

Barriers, supports, and effective interventions for uptake of human papillomavirus- and other vaccines within global and Canadian Indigenous peoples: a systematic review protocol

Abstract: BackgroundDespite the existence of human papilloma virus (HPV) vaccines with demonstrated safety and effectiveness and funded HPV vaccination programs, coverage rates are persistently lower and cervical cancer burden higher among Canadian Indigenous peoples. Barriers and supports to HPV vaccination in Indigenous peoples have not been systematically documented, nor have interventions to increase uptake in this population. This protocol aims to appraise the literature in Canadian and global Indigenous peoples, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 100 publications
0
18
0
Order By: Relevance
“…Measures of vaccine coverage are challenging to determine which make it difficult to quantify the impact of population-level vaccination protection [55] and highlights the importance of qualitative research in this area. Exact HPV vaccination numbers for communities included in this review are not known, coverage levels typically report levels from the general population and hide sub-populations, including Indigenous communities [55].…”
Section: Discussionmentioning
confidence: 99%
“…Measures of vaccine coverage are challenging to determine which make it difficult to quantify the impact of population-level vaccination protection [55] and highlights the importance of qualitative research in this area. Exact HPV vaccination numbers for communities included in this review are not known, coverage levels typically report levels from the general population and hide sub-populations, including Indigenous communities [55].…”
Section: Discussionmentioning
confidence: 99%
“…The number of patients diagnosed with cervical cancer has increased in recent years due to improvements of healthcare infrastructures and screening programs [2]. The current therapeutic strategies include surgical resection, conventional chemotherapy, radiotherapy, and human papillomavirus (HPV) vaccines [3, 4] and are effective against cervical cancer, but their curative effects are limited. Most patients with cervical cancer ultimately have cancer recurrence and metastasis, with subsequent mortality.…”
Section: Introductionmentioning
confidence: 99%
“…The review will include studies that have reported the prevalence of periodontal disease among Indigenous populations compared with non-Indigenous populations. This study will include Indigenous peoples from Australia (Aboriginal or Torres Strait Islanders), Canada (Inuit, Metes, First Nations), New Zealand (Maori), USA (American Indian and Alaskan Natives), Brazil (Amerindians, Xingu, Xavante Indians) and other countries, including but not limited to: China, South Asia, Southeast Asia, South America, Africa, Central America, Arabia, former Soviet Union, Scandinavia and the Paci c Islands [19]. Participants of all age groups, including children and adults, will be eligible for inclusion.…”
Section: Inclusion Criteria Participantsmentioning
confidence: 99%